ANALYSIS OF LOCAL GROUNDNUT PROCESSING ACTIVITY BY WOMEN IN KANO STATE, NIGERIA - SHUAIBU, H. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2021)
The study assessed groundnut processing activity by women in Kano State, Nigeria. Its objectives were to determine the profitability of the entrepreneurial activity, assess the contribution of the profit to women’s income and identify the constraints the women face in groundnut processing activity. The three agricultural zones of the State were used for the study. Each zone had six registered women groundnut processors groups. Four groups out of the six were randomly selected from each zone and used. Each group had 25 members per group and all the 25 members of each group were used for the survey to give a total sample size of 298 respondents (two questionnaires were not returned). Data were collected using interview schedule with the aid of questionnaire. The tools of the analysis employed for data interpretation were descriptive statistics, gross margin analysis and return on investment. The findings of the study revealed that monthly gross income of about N24,006.7 was obtained from groundnut processing with average return on investment of 26% and contributed about 94% to their total income. Major constraints perceived by the women was that the profit margin was low and cost of raw material was too high. It was concluded that groundnut processing by women in the study area was profitable though there is room for improvement when our finding is compared to other studies in other parts of the country. The study recommends the women to form cooperatives and buy the raw groundnut in bulk to take advantage of lower cost.